Bob, not Bob! - Scanlon, Elizabeth Garton; Vernick, Audrey (Disney-Hyperion, 2017)
"When a young boy gets a cold, he just wants his mommy. But his stuffy nose makes it difficult for him to call out to his mom--not 'Bob,' who happens to be the family dog"--